Body, masculinity and style in the upper-class youth of Lima - Villa, Julio (2015)
This paper approaches masculinity through the study of the body, taking into account its aesthetics tounveil a subject not well documented and to explore the experience and representation of masculinity in a socioeconomic sector that is not well known. The research on masculinities in Latin America and the world, point out three essential components: the persistent demonstration of masculinity; the distinction between feminine and homosexual; and the control of emotions. This research shows that, in the social sector explored, the concept of masculinity widens and the three components that were pointed out before, are reduced in intensity; meanwhile we foresee the importance of the body as an individuation factor and as an esthetic innovation. Through the practice of ethnography in two independent design stores in Lima, we observe that the appearance is produced when the personal taste, the salesmen as cultural intermediaries and the feminine figure intertwine.